2018
DOI: 10.1080/17482631.2018.1508171
|View full text |Cite
|
Sign up to set email alerts
|

Doctoral students’ well-being: a literature review

Abstract: Purpose: Doctoral student well-being is an important matter that shapes the well-being of academics throughout their careers. Given that well-being has been found to be closely related to employee productivity and efficiency, strategies associated with maintaining well-being during PhD studies might be crucial for higher education, its outcomes and—just as importantly—for a balanced life of PhD students. Method: Based on 17 studies, this literature review critically assesses the literature on doctoral student … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
186
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 189 publications
(195 citation statements)
references
References 79 publications
6
186
0
3
Order By: Relevance
“…Findings indicated that multidimensionality, complexity, and subjectivity were among the characteristics of well-being in HRP. These characteristics are also for the concepts of general well-being (60-62) as well as situation-specific well-being such as perinatal wellbeing and well-being in other disciplines (63,64). Yet, complexity, multidimensionality, and subjectivity are not unique to the concept of well-being; rather, many other concepts such as quality of life and comfort are multidimensional, complex, and subjective.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Findings indicated that multidimensionality, complexity, and subjectivity were among the characteristics of well-being in HRP. These characteristics are also for the concepts of general well-being (60-62) as well as situation-specific well-being such as perinatal wellbeing and well-being in other disciplines (63,64). Yet, complexity, multidimensionality, and subjectivity are not unique to the concept of well-being; rather, many other concepts such as quality of life and comfort are multidimensional, complex, and subjective.…”
Section: Discussionmentioning
confidence: 99%
“…Physical well-being also refers to functional ability and pertains to environmental factors such as facilities, equipment, and habitation standards (60). A former study into the well-being of doctorate students also found physical well-being, health maintenance, and work-life balance as the components of well-being (64). However, a study into the concepts of wellbeing and quality of life reported that the core of well-being is its psycho-spiritual dimensions, happiness, and inner energy and did not consider physical well-being as a key component of wellbeing (65).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Students completing a doctoral degree (hereafter, referred to as "PhD students") report struggling with feelings of social isolation, lack of motivation, and challenges with supervisors and the academic environment (Castelló, Pardo, Sala-Bubaré, & Suñe-Soler, 2017;Janta, Lugosi, & Brown, 2014;Lovitts, 2002;Sverdlik & Hall, 2019). Until recently, attention to such factors in the literature has been limited; research has tended to focus on how these factors predict completion and attrition rates (Lovitts & Nelson, 2000;Schmidt & Hansson, 2018;Sverdlik, Hall, McAlpine, & Hubbard, 2018). Further, although extant studies have measured some aspects of mental health-most commonly psychological distress-other aspects are not well-studied, including psychological well-being.…”
Section: Introductionmentioning
confidence: 99%
“…With high levels of well-being theoretically required to achieve a PhD degree, it is no surprise that low levels of well-being can have a substantial impact on PhD students' degree progress, professional development, research productivity and personal lives (Schmidt & Hansson, 2018). These problems, in turn, have administrative and financial implications for universities.…”
Section: Introductionmentioning
confidence: 99%